COMPARATIVE ANALYSIS OF PERCEIVED PRICE, PERCEIVED QUALITY AND PERCEIVED VALUE BETWEEN MALE AND FEMALE CUSTOMERS OF KFC IN MANADO - Bororing, Tirza; Lapian, S.L.H.V.Joyce; Tumiwa, Johan R. (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Human need to consume food to get energy in their daily activities. The development of franchise fast food restaurant is now growing rapidly and become very interesting phenomena in the Manado market. One of the fast-food restaurants are growing in Manado is Kentucky Fried Chicken (KFC). The purpose of this research is to analyze the differences between male and female customers of KFC in Manado determined from factors such as Perceived Price, Perceived Quality and Perceived Value. This research conducted by a quantitative method and the sample of this research is 100 respondents of KFC in Manado divided by 50 males and 50 females. By using an Independent Sample t-test, the result shows that there is significant difference between male and female customers in Perceived Price meanwhile there is no significant difference between male and female customers in Perceived Quality and Perceived Value. Based on the results, The Company should be more critical and more pay attention in order to re-structure their pricing strategy to compete with other fast food restaurants and just has to keep maintaining and improving the quality and value of the product/service to attract more new customers and to keep the loyal customers.Â ÂÂKeywords: perceived price, perceived quality, perceived value, independent sample t-test